Latest approaches for efficient protein production in drug discovery. (October 2014) - Sugiki, Toshihiko; Fujiwara, Toshimichi; Kojima, Chojiro
<x xml:space="preserve">Abstract</x> Introduction: Pharmaceutical research looks to discover and develop new compounds which influence the function of disease-associated proteins or respective protein–protein interactions. Various scientific methods are available to discover those compounds, such as high-throughput screening of a library comprising chemical or natural compounds and computational rational drug design. The goal of these methods is to identify the seed compounds of future pharmaceuticals through the use of these technologies and laborious experiments. For every drug discovery effort made, the possession of accurate functional and structural information of the disease-associated proteins helps to assist drug development. Therefore, the investigation of the tertiary structure of disease-associated proteins and respective protein–protein interactions at the atomic level are of crucial importance for successful drug discovery. Areas covered: In this review article, the authors broadly outline current techniques utilized for recombinant protein production. In particular, the authors focus on bacterial expression systems using Escherichia coli as the living bioreactor. Expert opinion: The recently developed pCold-glutathione S-transferase (GST) system is one of the best systems for soluble protein expression in E. coli. Where the pCold-GST system does not succeed, it is preferable to change the host from E. coli to higher organisms such as yeast expression systems like Pichia pastoris and Kluyveromyces lactis. The selection of an appropriate expression system for each desired protein and the optimization of experimental conditions significantly contribute toward the successful outcome of any drug discovery study.